2021
DOI: 10.1016/j.ufug.2021.127182
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distributive effects of public green space and COVID-19 infection in London

Abstract: While public green spaces (PGS) are opined to be central in the pandemic recovery, higher accessibility to PGS also mean a higher risk of infection spread from the raised possibility of people encountering each other. This study explores the distributive effects of accessibility of PGS on the COVID-19 cases distribution using a geo-spatially varying network-based risk model at the borough level in London. The coupled effect of social deprivation with accessibility of the PGS was used as an adjustment factor to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 35 publications
3
48
0
Order By: Relevance
“…Higher COVID-19 case incidence is associated with greater percentage of immigrants and lower education at the community level, likely due to occupational, medical, and housing risk factors that elevate risk of disease transmission and severity [16]. Likewise, environmental exposures, including air pollution and reduced green space, are associated with increased case incidence at the community level [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Higher COVID-19 case incidence is associated with greater percentage of immigrants and lower education at the community level, likely due to occupational, medical, and housing risk factors that elevate risk of disease transmission and severity [16]. Likewise, environmental exposures, including air pollution and reduced green space, are associated with increased case incidence at the community level [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these findings indicate that people with access to private green spaces such as gardens had greater nature contact during the pandemic. Private gardens acted as a safe green space without the risk of being exposed to the coronavirus while maintaining social distancing guidelines (Poortinga et al 2021;Shoari et al, 2020;Pan et al, 2021). This conclusion highlights the potential inequities in nature contact during lockdown because a larger share of the socioeconomically deprived population may not have had private or community gardens (Mell and Whitten, 2021;Natural England, 2020).…”
Section: Opportunities For Nature Exposurementioning
confidence: 96%
“…A few studies have speculated about the ways that nature accessibility and nature contact (e.g., visit frequency) might relate to COVID-19 transmission and case rates (Pan et al, 2021;Shoari et al, 2020;Lu et al, 2021b). Pan et al (2021) identified that higher nature accessibility in connected public parks was associated with a higher risk of COVID-19 infection rate in London boroughs.…”
Section: Covid-19 Incidence and Mortalitymentioning
confidence: 99%
See 2 more Smart Citations